ANÁLISE COMPARATIVA DOS NÍVEIS DE ATRITO EM BRÁQUETES CONVENCIONAIS E AUTOLIGADOS - Picchioni, Mauro dos Santos (2007)
The friction between brackets and orthodontic wires is an important issue to be considered concerning to orthodontic treatment efficiency in the sliding mechanics. Because this, always there are a search for ways to reduce the friction levels during this type of mechanics. With the introduction of self-ligated bracketts, it was observed that one of these devices main characteristics would be a reduction levels reduction of friction between brackets and wires, and because this the movement could be more efficient, with the application of low forces when compared the using of brackets with conventional ligation systems. The purpose of this study is compare by means of laboratorial tests, the esthatic friction coefficients of one esthetic self-ligated bracket, one metallic self-ligated bracket and two metallic conventional brackets, with the orthodontic wires of different materials, section and sizes, to determine which brackets presents the lowest coefficients of friction, in situations of different angulations between wires and brackets. The results had demonstrated that self-ligated brackets had presented a static friction significantly lower at situations whitout angulation between the wire and brackets and when using small size wires, with more flexible material, when compared with conventional brackets. The metallic self-ligated bracket presented more friction, similar the conventional brackets, with the use larger diameter wires, without angulation between bracket and wire. The metallic self-ligated bracket presented higher static friction when compared with conventional brackets, with the use larger diameter wires, at situations with angulation betwen bracket and wire.